The Role of Semantic Mapping Strategy in Helping the Students to Write Descriptive Text Easily - Abdul Aziz Rifa’at (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Semantic mapping strategy is an effective strategy in helping the students to start their writing. This strategy is applied at the beginning of writing. The aim of this study was to find out the significant difference in writing achievement of the 10th graders at SMA Islam Al-Amalul Khair in the academic year 2020-2021 before and after this strategy was applied. The pre-experimental method was used in this study. The population and sample in this study was all of 10th graders at SMA Al-Amalul Khair Palembang in academic year 2021-2020-2021. The total number of them was 61 students. The test was administered twice as pre-test and post-test. The results of the tests were analyzed by using a t-test through SPSS (Statistical Package for Social Sciences) program. The result of the study showed that there was a significant difference in the writing achievement of 10th graders at SMA Al-Amaluul Khair Palembang before and after the semantic mapping strategy was applied.